Novel Interaction Techniques for Mobile Augmented Reality Applications – A Systematic Literature Review - Härkänen Lauri; Helle Seppo; Järvenpää Lauri; Lehtonen Teijo (University of Turku Technical Reports, No.9, 2025)
This study reviews the research on interaction techniques and methods that could be applied in mobile augmented reality scenarios. The review is focused on the most recent advances and considers especially the use of head-mounted displays. In the review process, we have followed a systematic approach, which makes the review transparent, repeatable, and less prone to human errors than if it was conducted in a more traditional manner. The main research subjects covered in the review are head orientation and gaze tracking, gestures and body part tracking, and multimodality– as far as the subjects are related to human-computer interaction. Besides these, also a number of other areas of interest will be discussed.